Magnesium sulfate improves blood flow of uterine, umbilical, and fetal middle cerebral arteries in women with severe preeclampsia at 30-34 gestational weeks - Baoxiang Xing; Xie Dai; Guoqiang Gao; Ling Liu; Yan Zhang (Taylor & Francis Group, 2024)
Objectives Magnesium sulfate (MgSO4) is one of the most commonly used agents for the treatment and prophylaxis of eclampsia in patients with severe preeclampsia. However, there is no international consensus regarding the optimal gestational age for MgSO4 treatment. The aim of this study was to assess the effect of MgSO4 on uterine (UtA), umbilical, and fetal middle cerebral arteries (MCA) by calculating the SD ratio (S/D), resistance index (RI), and pulsatility index (PI) at different gestational weeks.Methods In total, 66 pregnant women as participants with severe preeclampsia were divided into two groups based on gestational age: Group 1 (n = 28, 26-30 weeks) and Group 2 (n = 38, 30-34 weeks). Color Doppler (Philip HD11) measurements were taken and compared before and after the MgSO4 loading dose.Results Within-group analysis revealed significant differences in RI-UtA, PI-UtA, and S/D in UtA before and after MgSO4 administration in Group 1. Furthermore, the RI-UA and RI-MCA decreased statistically significantly after MgSO4 treatment, whereas the pulsatility index and S/D did not change in either the umbilical or middle cerebral arteries. After MgSO4 treatment, all Doppler parameters in the uterine and umbilical arteries in Group 2 showed significant changes when compared to before MgSO4 administration.Conclusion MgSO4 can effectively improve umbilical and MCA blood flow at 30-34 gestational weeks but not at 26-30w. Meanwhile, using MgSO4 can improve uterine blood flow in severe preeclampsia, which may contribute to the management of reducing adverse events in pregnant women who have preeclampsia and fetal growth restriction.